2021
DOI: 10.1002/ange.202100369
|View full text |Cite
|
Sign up to set email alerts
|

Prodrug Activation by Gold Artificial Metalloenzyme‐Catalyzed Synthesis of Phenanthridinium Derivatives via Hydroamination

Abstract: An emerging approach in the field of targeted drug delivery is the establishment of abiotic metal‐triggered prodrug mechanisms that can control the release of bioactive drugs. Currently, the design of prodrugs that use abiotic metals as a trigger relies heavily on uncaging strategies. Here, we introduce a strategy based on the gold‐catalyzed activation of a phenanthridinium‐based prodrug via hydroamination under physiological conditions. To make the prodrug strategy biocompatible, a gold artificial metalloenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Stimulus-responsive prodrugs that involve metal ions can exhibit similar limitations, where efficient prodrug activation with external stimuli and close control of pharmacokinetics remains challenging and therefore represents a current area of research interest. Strategies such as transition metal-mediated, cell-compatible catalysis, or photodynamic triggering for drug activation or release have shown efficacy. However, the dependence on an external stimulus or catalyst concentration can pose significant limitations on the accessibility or threshold abundance of the biological target. …”
Section: Introductionmentioning
confidence: 99%
“…Stimulus-responsive prodrugs that involve metal ions can exhibit similar limitations, where efficient prodrug activation with external stimuli and close control of pharmacokinetics remains challenging and therefore represents a current area of research interest. Strategies such as transition metal-mediated, cell-compatible catalysis, or photodynamic triggering for drug activation or release have shown efficacy. However, the dependence on an external stimulus or catalyst concentration can pose significant limitations on the accessibility or threshold abundance of the biological target. …”
Section: Introductionmentioning
confidence: 99%
“…The second transformation is catalyzed by a Buchwald‐type Au I ‐phosphine complex ( Au3B ), which we introduce here as a novel bioorthogonal catalyst. Similar gold complexes have been applied as I) gold‐anion sensors [24, 25] and II) in the field of artificial metalloenzymes and biorthogonal catalysis [20, 26, 27] . The resulting reaction cascade combines both major mechanisms of (bio)‐precursor prodrug activation: an initial bond cleavage step is followed by a subsequent bond‐forming step [28] .…”
Section: Introductionmentioning
confidence: 99%
“…Since the emergence of sequential bimetallic transformations as useful approaches to building complex molecules in one pot without the need to isolate intermediates, we now followed the idea of transforming our construct into a novel nanoreactor capable of performing a two‐step bimetallic reaction sequence in aqueous systems and biorelevant media. Since heterocyclic scaffolds remain at the heart of many medicinally important molecules, we focused on the synthesis of indoles and phenanthridines as important scaffolds for natural products as well as anticancer and antimicrobial drugs [18–23] …”
Section: Introductionmentioning
confidence: 99%
“…As such, the hydrophilic GSH molecules apparently cannot reach the complex when it is inside the hydrophobic cavity of the protein. In A549 cells it was shown that while high concentrations of gold complex were needed to synthesize the cytotoxic compound and induce cell death, much lower concentrations of metalloenzyme were needed to achieve the same levels of cytotoxicity, indicating that protection of the gold catalyst with the protein scaffold can prevent catalyst poisoning and improve reactivity [8] . This incompatibility of gold complexes with the cellular environment runs both ways.…”
Section: Introductionmentioning
confidence: 99%
“…In A549 cells it was shown that while high concentrations of gold complex were needed to synthesize the cytotoxic compound and induce cell death, much lower concentrations of metalloenzyme were needed to achieve the same levels of cytotoxicity, indicating that protection of the gold catalyst with the protein scaffold can prevent catalyst poisoning and improve reactivity. [8] This incompatibility of gold complexes with the cellular environment runs both ways. Cellular biomolecules have a detrimental effect on the catalytic activity, but gold complexes can also harm the cells by inducing toxicity themselves.…”
Section: Introductionmentioning
confidence: 99%